Chaotic genetic patchiness in the pelagic teleost fish Sardina pilchardus across the Siculo-Tunisian Strait. Issue 4 (20th April 2020) - Deli, Temim; Guizeni, Souad; Ben Abdallah, Lotfi; Said, Khaled; Chatti, Noureddine
ABSTRACT: This investigation aims at assessing patterns of spatial genetic structure of the teleost fish Sardina pilchardus across the Siculo-Tunisian Strait (a well-known discontinuous biogeographic area) and delineating putative genetic stocks within the species. For this purpose, a total of 180 specimens, collected from 11 locations stretching across the western and eastern Mediterranean coasts of Tunisia, were analysed genetically by means of 18 nuclear allozyme loci. The outcome of this study revealed strong genetic differentiation among populations, with the marked genetic distinctiveness of the central Tunisian population at Mahdia. Despite the delineation of seven well-defined genetic groups, no significant correlation was found between genetic and geographic distances. Besides, the recorded population subdivision did not align with biogeographic boundaries, suggesting the presence of chaotic genetic patchiness. Recent genetic bottlenecks were evidenced in S. pilchardus populations. Patchy migration patterns were recorded among the examined pairs of sardine populations. Among the recorded 16 polymorphic loci, GPI-2 and SOD appeared to be subject to natural selection. Patterns of population genetic differentiation and structuring were not found to be driven by outlier loci that appeared to be under selection. Furthermore, the detected neutral GPI-1 locus was found to be responsible for most of the genetic variation among identified genetic clusters. Hence, natural selection cannot cause the detected genetic heterogeneity among sardine samples. Different explanations to the origin of chaotic genetic patterns, observed within S. pilchardus, were discussed.